PERILAKU HIPERAKTIF ANAK USIA DINI DAN POLA ASUH MENGATASINYA - Susita Hartati (Conciencia, 2015)
Hyperactivity is a term that is found in a child's personality, which sometimes makes parents and teachers upset, resentful, even angry especially those for those who do not have adequate knowledge about it. Consequently, in addressing parenting, neither by scientifically, but it is done with conventional approaches. Hyperactivity can be distinguished by tuna barrel, although the two terms are equally present in a child's personality early age. Hyperactivity has its own characteristics in many aspects of behavior, as well as a tuna barrel, should have a fundamental understanding of the two can provide solutions to overcome them. Knowing the cause of its emergence into something that is very important in dealing with a hyperactive child. But if it has happened, then understand parenting should be given to children is much more important before addressing the symptoms of his hyperactivity. Parenting with a variety of patterns, such as the theory Baumrende consists of three kinds, namely authoritarian, permissive and outoritatif is an alternative in providing services addressing hyperactive behavior, although a specific strategy by a teacher who is personal can be adopted, and is something that is no less important, especially in modifying the behavior of a child. A strategy that in the psychology of learning termed hyperactive children trap behavior.